Impact of the agglomeration process on structure and functional properties of the agglomerates based on the durum wheat semolina. (January 2015) - Hafsa, I.; Mandato, S.; Ruiz, T.; Schuck, P.; Jeantet, R.; Mejean, S.; Chevallier, S.; Cuq, B.
Highlights: Innovative ways to agglomerate durum wheat semolina. Agglomerates were produced by using pneumatic or mechanical mixing technologies. The process conditions control the internal microstructure of the agglomerates. A mechanistic model describes the reversible/irreversible mechanisms. Abstract: The agglomeration process controls the structure characteristics and end-use properties of the agglomerates. Understanding the mechanisms involved in the structuration of the food agglomerates still represents a real scientific stake. The objective of the present study is to improve the knowledge of the process–structure–properties relationships for the agglomeration of the durum wheat semolina. Pneumatic and mechanical agglomeration technologies were selected to generate different hydro–thermo–mechanical stresses during process. The agglomerates were characterized by their structures (electron microscopy, compactness, X-ray micro-tomography, starch gelatinization) and functional properties (colors, flowability, swelling, water solubility index). The results demonstrate specific effects of shear rate, process duration, and temperature on the physicochemical mechanisms occurring during processing. A functional mechanistic model was proposed to improve the description of the agglomeration mechanisms by considering the reversible and irreversible changes. This offers innovative potential to design new agglomeration processes by considering the physicochemical reactivity of the food powders.